1994
DOI: 10.1007/bf01411011
|View full text |Cite
|
Sign up to set email alerts
|

QCD studies using a cone-based jet finding algorithm fore + e ? collisons at LEP

Abstract: We describe a cone-based jet nding algorithm (similar to that used in pp experiments), which we have applied to hadronic events recorded using the OPAL detector at LEP. Comparisons are made between jets de ned with the cone algorithm and jets found by the \JADE" and \Durham" jet nders usually used in e + e experiments. Measured jet rates, as a function of the cone size and as a function of the minimum jet energy, have been compared with O( 2 s ) QCD calculations, from which two complementary measurements of s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 72 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…For W þ 1, 2-jet production we have confirmed that distributions using SISCONE are within a few percent of those obtained with MCFM using the midpoint cone algorithm [83]. (The midpoint algorithm is infrared-safe at NLO for W þ 1, 2-jet production, but not for W þ 3-jet production [37].)…”
Section: Tevatron Resultssupporting
confidence: 67%
“…For W þ 1, 2-jet production we have confirmed that distributions using SISCONE are within a few percent of those obtained with MCFM using the midpoint cone algorithm [83]. (The midpoint algorithm is infrared-safe at NLO for W þ 1, 2-jet production, but not for W þ 3-jet production [37].)…”
Section: Tevatron Resultssupporting
confidence: 67%
“…Unlike the factorization scales that we will discuss shortly, µ ⊥ is not introduced to renormalize the fragmentation functions but to define the perturbative (or non-perturbative) part of the dihadron fragmentation functions. It is quite analogous to the cone-size of jet definitions [19].…”
Section: The Parton Modelmentioning
confidence: 93%
“…In each e v ent, charged tracks and those electromagnetic clusters not associated to charged tracks, were grouped into jets using the jet cone algorithm described in [10] with cone half angle R = 0 : 7 rad and minimum jet energy = 7 : 0 GeV. It was required that the two highest energy jets be in opposite hemispheres, where the hemispheres are dened with respect to the thrust axis calculated using the same tracks and clusters as used in the jet nding.…”
Section: Event Selection and Monte Carlo Simulationmentioning
confidence: 99%